Use of complementary DNA oligomers to probe trp leader transcript secondary structures involved in transcription pausing and termination. - Fisher, R (1984)
DNA oligomers were synthesized that are perfectly complementary to different segments of the tryptophan (trp) operon leader transcript. These 15 nucleotide long oligomers were used as probes of the involvement of transcript secondary structures in two processes: transcription pausing at the pause site located near base pair 90 in the leader region, and transcription termination at the attenuator. The 15-mers were complementary to the four segments of the trp leader transcript which have been shown to form the alternative secondary structures that are believed to be responsible for pausing, termination, and antitermination. Oligomers complementary to RNA segments 1 and 3 relieved termination while the 15-mer complementary to RNA segment 1 relieved pausing. 15-mers complementary to segment 2 had no effect on pausing and the oligomer complementary to segment 4 had virtually no effect on termination.